Controlled Air Oxidation of Plastic and Biomass in a Packed‐Bed Reactor. Issue 1 (10th December 2013) - Meng, Qingmin; Chen, Xiaoping; Bu, Changsheng; Ma, Jiliang
Abstract A packed‐bed reactor was established to study the effect of polypropylene (PP) content on the controlled air oxidation performance of a mixture of PP and sawdust (SD) at a fixed feed gas flow rate. Attention was focused on product yields, evolutionary behavior of the gas flow rate, and gas compositions. A higher PP content led to increased gas yield, lower solid yield, and substantially reduced liquid yield. The PP content significantly affected the gas composition and rate of gas production. Mixtures of plastic and biomass can be radically converted to gaseous and liquid products under controlled air oxidation conditions.